(untitled) (Selecciones Matemáticas, 2017)
In this paper we present an estimate of the posterior error of ﬁnite element-constructed ﬁnite element meshes and ﬁnite element discontinuous over time for the transport equation of CO2 in the bags Alveolar cells of the human lung, using the dual weighted residual method (DWR).